Novel copoly(styrene-divinylbenzene)-resins with different phenylmethylamine groups for use in peptide synthesis method - Souza, Sinval E.G.; Malavolta, Luciana; Cilli, Eduardo M. [UNESP]; Schreier, Shirley; Jubilut, Guita N.; Nakaie, Clovis R. (Bentham Science Publishers, 2015)
Differently than the 4-methylbenzhydrylamine-resin (MBHAR) which contains a methyl group coupled to the phenylmethylamine-functionalized copoly(styrene-divinilbenzene) structure, alternative resins containing the electron-donating 4-tert-butyl-(BUBHAR) or the electron-withdrawing 2-chloro-(ClBHAR) and 2,4-chloro-(diClBHAR) groups were developed as potential supports for α-carboxamide peptide synthesis. Initially, a time-course investigation of HF cleavage reaction (0 °C) with these resins bearing the vasoconstrictor angiotensin II (AngII, DRVYIHPF) or its Gly8-AngII analogue revealed that the peptide-BUBHAR linkage is much more labile than those with ClBHAR or diClBHAR. HF cleavage times of near 2 h or longer than 24 h were needed for complete removal of peptide chains from these two classes of resin, respectively. By including MBHAR and benzhydrylamine-resins (BHAR) in this comparative study, the decreasing order of acid stability of the peptidyl-resin linkage was diClBHAR >ClBHAR >BHAR >MBHAR ∼ BUBHAR. The same stability order was observed for the HCl/propionic acid hydrolysis reaction (130°C) with the Phe-or Gly-resins. These findings thus suggest that ClBHAR and diClBHAR are not appropriate for use in peptide synthesis. Nevertheless, these supports could still be tested as stationary phases for affinity chromatography. When placed into more apolar solvents, the beads of all of these resins exhibited a greater swelling (as measured by a microscope) or higher mobility of the polymer matrix (as measured with EPR experiments using spin-labeled beads). Moreover, under the latter approach, BUBHAR displayed a comparatively higher solvation degree than did MBHAR (in DCM, DMF and NMP), with slightly higher peptide synthesis yields as well.
Keywords: Copolymer; Electron paramagnetic resonance; Methylbenzhydrylamine-resin; Peptide synthesis; Peptide-resin cleavage; Polymer; Resin; Spin label